2018
DOI: 10.1016/j.jpedsurg.2018.02.086
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental necrotizing enterocolitis with stem cell-derived exosomes

Abstract: Basic science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 28 publications
1
78
0
Order By: Relevance
“…Although it has been shown that several different types of SC reduce the incidence and severity of experimental NEC, SC research in clinical medicine is difficult and faces many ethical, legal, and scientific challenges, including a theoretical concern for potential tumorigenicity [2]. This concern led to a follow-up study, which examined EVs released from SC and their ability to protect the intestines from NEC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it has been shown that several different types of SC reduce the incidence and severity of experimental NEC, SC research in clinical medicine is difficult and faces many ethical, legal, and scientific challenges, including a theoretical concern for potential tumorigenicity [2]. This concern led to a follow-up study, which examined EVs released from SC and their ability to protect the intestines from NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing enterocolitis (NEC) is a devastating disease of newborns, with mortality rates that remain as high as 20%-30%. The cost of treating infants with NEC exceeds $1 billion in the US each year [2]. Babies who survive NEC frequently have long term complications including short bowel syndrome, developmental delays and neurological sequelae [1][2][3].…”
mentioning
confidence: 99%
See 3 more Smart Citations